Productive Waqf as a Sustainable Model Integrating Islamic Finance, Investment, and ESG Principles - Riyan Damara Putra; Syamsul Hilal; Fatih Fuadi; Hotman (Jurnal Riset Perbankan Syariah, 2026)
This study examines productive waqf as an ESG-based Islamic finance model by integrating Islamic social finance, sharia-compliant investment, and sustainability-oriented governance. Although waqf has historically supported public welfare, many waqf assets remain underutilized because they are still managed through passive and charity-oriented approaches. Using a qualitative design, this study conducts a systematic literature review of Scopus-indexed publications, supported by thematic synthesis and conceptual modeling. The analysis identifies five interconnected dimensions that determine the effectiveness of productive waqf: governance, investment mechanisms, social impact orientation, sustainability integration, and institutional performance. The findings show that governance strengthens accountability, transparency, and institutional trust, while sharia-compliant investment mechanisms transform waqf assets into sustainable financial resources. ESG integration further enhances productive waqf by aligning economic activities with ethical, social, and environmental objectives. This study contributes to Islamic economics and sustainable finance literature by proposing a systems-based framework that positions productive waqf as a strategic model for generating long-term financial, social, and environmental value.